Statistical Approach to Quantum Field Theory: An Introduction - Wipf, Andreas (Lecture Notes in Physics, 2013)
This book opens with a self-contained introduction to path integrals in Euclidean quantum mechanics and statistical mechanics, and moves on to cover lattice field theory, spin systems, gauge theories and more. Each chapter ends with illustrative problems.